Landscape ecological risk assessment across different terrain gradients in the Yellow River Basin - Yan, Jixuan; Qiao, Hongqiang; Li, Qiang; Song, Miao; Yao, Xiangdong; Gao, Pengcheng; Zhang, Meihua; Li, Jie; Qi, Guangping; Li, Guang (Frontiers in Environmental Science, 2024)
The Yellow River Basin is an important ecological barrier zone in China, and the landscape pattern has changed greatly due to intense human activities. It is of great significance to explore the dynamic forecasting of ecological risk based on terrain gradient for the ecological security of the Yellow River Basin. In this study, the distribution characteristics of ecological risk from 2000 to 2040 are evaluated by CA-Markov and ERI models. We put forward a new method of landscape ecological risk assessment based on terrain gradient and further analyzed the relationship between ecological risk and terrain index. The results showed that the proportion of the cultivated land and the grassland in the Yellow River basin is more than 73%, with the largest dynamic change in 2020. The ecological risk in the study area showed a spatial pattern of ‘high in the northwest and southwest, low in the east and south-central’. During the study period, the overall ecological risk showed a decreasing trend, and the high risk was reduced by four times. The future ecological risk of all terrain gradient will show a decreasing trend, the high risks mainly occurred in areas with ‘flat terrain with low terrain gradient and low vegetation coverage’. This study will provide a new perspective for the dynamic forecasting of ecological risk and the analysis of the change of ecological risk through terrain gradients.